Creativity in higher education of nursing - from the theoretical concepts to the pedagogical effects - Onã Silva; Elioenai Dornelles Alves; Maria Cristina Soares Rodrigues (Universidad de Alicante, 2015)
Objective: This article aims to reflect on creativity in nursing education, basing on theories, discussing the applicability and pedagogical creative effects, in educational actors. Method: It is the original study of reflection. The study was led by reflective thinking using the operator cognoscente of the complexity theory, by Edgar Morin. Related theories were selected for creativity and convergent in the sociocultural approach: the Theory on Systems Perspective, the General Theory for the Development of Creative Productivity in Young People and the Science of Unitary Human Being. Results: The theoretical conceptions of the study contribute to production of science regarding creativity in higher education, overcoming the scientific gaps in the subject. The theories substantiate and present scientific relevance to the researches and to the pedagogical evidence. Pedagogical effects of teaching based on creativity, for educational actors, teachers and students most identified were autonomy, independence, divergent thinking, unusual ideas, joy and others. Conclusion: The theoretical conceptions of creativity contribute to nursing knowledge, enriching the care actions, since the teaching, favoring the potential creator of professionals.